[PP.03.21] RELATIONSHIP BETWEEN DYSLIPIDEMIA AND URINARY ALBUMIN EXCRETION IN HYPERTENSIVE ADULTS: A NATIONWIDE POPULATION-BASED STUDY. (September 2016) - KIM, D.; Lee, S.; Kim, Y.; Roh, Y.; Ju, S.; Nam, H.; Nam, G.; Choi, J.; Lee, J.; Sang, J.; Han, K.; Park, Y.
Abstract : Objective: This study aimed to estimate the relationship between various lipid abnormalities and albuminuria in hypertensive Korean adults. Design and method: Data obtained from the Korean National Health and Nutrition Examination Survey in 2011–2012 were analyzed. The study included 2, 330 hypertensive participants. Total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were measured. Lipid abnormalities were defined as high TG (TG > = 200 mg/dL), low HDL-C (HDL-C < 40 mg/dL), high TC/HDL-C (ratio > = 5), high TG/HDL-C (ratio > = 3.8), and high LDL-C/HDL-C (ratio > = 2). Albuminuria was defined as a urine albumin to creatinine ratio (ACR) > = 30 mg/g. Results: Women with albuminuria showed significantly higher levels of TG, TC/HDL-C, and TG/HDL-C and a lower level of HDL-C than women without albuminuria (all p < 0.05). TG, TC/HDL-C, and TG/HDL-C were positively correlated with ACR in both men and women; however, HDL-C was negatively correlated with ACR in women and non-HDL-C was positively correlated with ACR in men. In men, there was no association between ACR and lipid parameters. However, in women, higher values for log TG, TC/HDL-C, and log TG/HDL-C were associated with an increased odds ratio for albuminuria (odds ratio [95% confidence interval]: 1.54 [1.04–2.28], 1.22 [1.04–1.43], and 1.80 [1.20–2.71], respectively) and HDL-C with a decreased odds ratio for albuminuria (0.78 [0.67–0.92]) after adjusting for all covariates. Conclusions: High TG, TC/HDL-C, and TG/HDL-C were associated with an increased prevalence of albuminuria in hypertensive women. Screening and treatment for dyslipidemia may be necessary for hypertensive women to address potential albuminuria.